Dermatophytosis: A Report from Tertiary Care Hospital in Davanagere, Karnataka, India - Mangala, G.K.; Chandrappa, N.R.; Vijayanath, V. (Research Perspectives of Microbiology and Biotechnology Vol. 3, 2024)
Background: Dermatophytosis refers to superficial fungal infection of keratinized tissue caused by Dermatophytes. It is more prevalent in tropical and subtropical countries including India where heat and moisture play an important role in promoting the growth of these fungi. Dermatophytosis though not life threatening, its severity should not be underestimated as it can cause great discomfort and at times cause disability and disfigurement. So laboratory investigations are important for correct diagnosis, management and minimizing cost. Objective: The present study was undertaken to know the clinico-mycological profile of dermatophytic infection, prevalence of various species, the co-relation between the site of involvement and causative agent and to compare KOH smear positivity with culture positivity. Design: Prospective observational study. Methods: Samples from total of 200 clinically diagnosed cases of dermatophytosis were subjected to microscopy with 10%KOH, fungal culture on SDA agar and further identification of the species based on standard tests. Results: Out of 200 cases, Tinea corporis 89 cases (44.5%) was the commonest clinical presentation followed by Tinea cruris. The common species isolated was Trichophyton rubrum 86(65.2%) followed by Trichophyton mentagrophytes 28(21.2%). Conclusion: The present study gives valuable insight into the clinical and mycological pattern of superficial fungal infections in this region as well as shows the importance of mycological examination of dermatophytosis samples for planning effective management.